THE CONCEPTUAL FEATURES OF THE LABOUR MARKET OF SINGLE-INDUSTRY TOWNS - O. A. Kolesnikovа; V. A. Pohvoschev (Модернизация, инновация, развитие, 2015)
The article discusses the possibility of program-oriented management of the development of the economy. Outlines the methodological foundations of Management by Objectives and show their perfection in accordance with the growing scale and complexity of controlled processes. The experience of applying these methods in theUSSR, the industrialized countries and inRussia. There is an incomplete utilization of program-oriented management in theUSSRand theRussian Federationand the shortcomings in addressing socio-economic and scientifictechnological problems. To account for the uncertainty generated by the goals and ways to achieve them are invited to share the goal of two series connected subsets: ongoing and planned. The necessity and the possibility of reconciliation and the interests of performers and program managers in general. The possibilities for improving the methodology and its effective use in a market economy inRussiaand outside calls.